PHYSICS AND HEALTH: BODY TEMPERATURE, BLOOD PRESSURE, AND HEART RATE - Rahimova Zebiniso Olimjon qizi; Ahmadjanova Nigora Akramjon qizi; Abdulboriyeva Xurshida Abdulla qizi (International Scientific and Current Research Conferences, 2025)
This article analyzes the main physiological processes in the human body – body temperature, blood pressure, and heart rate – based on physical laws. These indicators are crucial factors determining the overall health, internal balance, and life activity of the organism. Each process is explained according to the corresponding physical laws of thermodynamics, hydrodynamics, and electrophysiology, and modern medical technologies used to monitor and measure these indicators are discussed. A systemic approach reveals the integral connection between physics and medicine, highlighting innovative opportunities in the field of healthcare.